Testing Long-Run Neutrality Of Money In A Developing Economy - Muzafar Shah, Habibullah; Puah, Chin Hong; Azali, M. (Giordano Dell-Amore Foundation, 2002)
Monetary aggregates movements and their influence on domestic economy are important and essential to policymakers and researchers. To the policymakers, the influence and the existence of special relationship between monetary aggregates and other macroeconomic variables are important in designing policies such as to curb inflation pressure, stimulating economic growth and reduce unemployment problem. On the other hand, the researchers may use these aggregates and the irrelations with macroeconomic variables to estimate a complex macro model of an economy.